THE ANALYSIS OF THE FIFTH SEMESTER ENGLISH DEPARTMENT STUDENTS CASUAL CONVERSATION OF TIDAR MAGELANG UNIVERSITY IN THE ACADEMIC YEAR 2008/2009 - Karma, C. Prima Ferri (Majalah Transformatika, 2009)
I conducted the study to depict the casual conversations outside the class and aspects of communicative competence of fifth semester students of Education and Teachers Training Faculty, University of Tidar Magelang. The campus was chosen to be the setting of the study. When conversations progressed however some students tended not to prolong the conversation because of their incapability of using speech functions. The problem statements of the study are: what speech functions are displayed  in students  casual conversations, how are conversations between students structured, and what negotiation techniques are mostly used by the students to sustain their conversations. The  data  analysis  was  based  on  the  concept  of speech functions network which is proposed by Eggins and Slades. Concerning speech function, interaction in terms of conversation might be organized into opening, continuing, and sustaining which covers responding and rejoinder.   Key words: analysis, casual, conversation